Produção de fitomassa e acúmulo de nutrientes por espécies adubadeiras em um Sistema Agroflorestal Sucessional - Santos, Rafael Virginio dos (2019)
The inclusion of “fertilizer” species in Successional Agroforestry Systems (SAFS) may reduce the use of fertilizers and pesticides. The species called “fertilizers” in this work promote improvements in the physicochemical, water and biological properties of soils, reducing production costs and contributing to the lower dependence of farmers on time and space. This paper aims to answer the following question: What is the contribution of “fertilizer” species to nutrient cycling in a Successional Agroforestry System. The objective of this work was to evaluate the production of Aerial Phytomass (FA) and the nutrient accumulation of four species destined for green manure (fertilizers) in a SAFS, from September 2017 to July 2018, in the Settlement Luiz Beltrame, in Gália, SP. The treatments were four species: Musa paradisiaca L. cv BRS Tropical, T2 - Cajanus cajan Mill sp. cv broad bean; T3 - Inga striata Benth. and 4 - Megathyrsus maximus Jacq., Cv mombaça. The species Musa paradisiaca produced higher amount of FA and accumulated more nutrients during the evaluated period when compared to the other species. The species Cajanus cajan Mill sp., Inga striata Benth. and Megathyrsus maximus Jacq. did not differ regarding the accumulation of P and Mn in AF. Also for the accumulation of CO the species Inga striata Benth. and Megathyrsus maximus Jacq. did not differ from each other.